Composición nutricional de diez genotipos de lupino (L. mutabilis y L. albus) desamargados por proceso acuoso - Quispe Sanca, David (2015)
The largest number of genotypes of L. mutabilis are in Perú. All of them need to be debittered (elimination of toxic alkaloids) before consumption, by aqueous washing. However, there is no information about the genotype effect on this process, neither on the compositional changes or the alkaloid levels of reduction, which is needed for nutritional estimations and safety. This research focused on the evaluation of nine genotypes of L. mutabilis from different regions, and one L. albus cultivated locally studied as a comparison. Weight gain in hydrated grain, dry matter loss, and proximal analysis were determined. Also carbohydrates, oligosaccharides, soluble protein, antioxidant activity and residual total alkaloids by spectrophotometric methodologies. The debittered genotypes increased twice its wet weight, yield after drying was 74%, and a 26% dry matter reduction was observed. In proximal composition, debittered genotypes behavior was similar (increased crude protein and fiber and decreased carbohydrates and ash) with the exception of fat composition changes. Antioxidant activity and oligosaccharides of genotypes was reduce after debittering in a range of 10 to 60%. Total alkaloids were decreased in 97% of its original content. This information will allow producers and consumers to estimate nutritional benefits of processed grains.